2018
DOI: 10.1103/physrevlett.120.155301
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Coupled Dynamics of the Two-Fluid Model in Superfluid He4 : Deformed Velocity Profile of Normal Fluid in Thermal Counterflow

Abstract: The coupled dynamics of the two-fluid model of superfluid ^{4}He is numerically studied for quantum turbulence of the thermal counterflow in a square channel. We combine the vortex filament model of the superfluid and the Navier-Stokes equations of normal fluid. Simulations of the coupled dynamics show that the velocity profile of the normal fluid is deformed significantly by superfluid turbulence as the vortices become dense. This result is consistent with recently performed visualization experiments. We intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…The result is qualitatively consistent with the one-ring simulation [41]. The normalfluid vortex structure smaller than the mean spacing of the filaments was not examined in the preceding simulation [45].…”
supporting
confidence: 81%
See 3 more Smart Citations
“…The result is qualitatively consistent with the one-ring simulation [41]. The normalfluid vortex structure smaller than the mean spacing of the filaments was not examined in the preceding simulation [45].…”
supporting
confidence: 81%
“…However, the model does not describe the dynamics of quantized vortices although it is essential for QT. The other method is to employ the VFM for the superfluid coupled with the HVBK equations for the normal fluid [41][42][43][44][45]. Kivotides et al performed simulation of a propagating quantized-vortex ring and indicated that two vortex rings of the normal fluid are produced around the quantized vortex [41].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments [8] use wider channels; in practice the velocity profile of the normal fluid differs generally from the Poiseuille form [8]; and in practice the vortex lines in the superfluid component are likely to suffer drag or pinning at the solid boundaries. Simulations that take account of these differences are starting to be practicable [22], and could eventually allow more satisfactory comparison with experiment.…”
Section: Dissipation In a Random Vortex Tangle: Simulations Relatmentioning
confidence: 99%